Regular and Young Investigator Award Abstracts 2020
DOI: 10.1136/jitc-2020-sitc2020.0098
|View full text |Cite
|
Sign up to set email alerts
|

98 ATA3271: an armored, next-generation off-the-shelf, allogeneic, mesothelin-CAR T cell therapy for solid tumors

Abstract: BackgroundMesothelin (MSLN) is a glycosylphosphatidylinositol (GPI)-anchored membrane protein with high expression levels in an array of malignancies including mesothelioma, ovaria, non-small cell lung cancer, and pancreatic cancers and is an attractive target antigen for immune-based therapies. Early clinical evaluation of autologous MSLN-targeted chimeric antigen receptor (CAR)-T cell therapies for malignant pleural mesothelioma has shown promising acceptable safety1 and have recently evolved with incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The most relevant translational question is whether 1XX modification is also beneficial against solid tumors. Though a prior study reported the 1XX design of a mesothelin-targeting CAR was effective in a pleural mesothelioma mouse model [22] , there was no direct comparison with its WT counterpart and the underlying molecular mechanism were not investigated. Our study demonstrated that 1XX modification can enhance CAR-T cell efficacy against solid tumors in two different CAR settings and tumor models, suggesting this could be a general optimization strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant translational question is whether 1XX modification is also beneficial against solid tumors. Though a prior study reported the 1XX design of a mesothelin-targeting CAR was effective in a pleural mesothelioma mouse model [22] , there was no direct comparison with its WT counterpart and the underlying molecular mechanism were not investigated. Our study demonstrated that 1XX modification can enhance CAR-T cell efficacy against solid tumors in two different CAR settings and tumor models, suggesting this could be a general optimization strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, allogeneic 'off the shelf' MSLN-targeted CAR T cells are being developed. They are yet to be tested in the clinical setting for MPM, but preclinical studies have shown encouraging results so far [145,146]. Another approach not yet tried against MPM is the genetic modification with an anti-MSLN CAR of other types of immune cells such as macrophages [147] and natural killer cells [148,149].…”
Section: Mesothelin-targeted Cellular Therapymentioning
confidence: 99%